Cloning - Harris, Nancy, 1952- (Detroit : Thomson Gale, 2005)
Anthologies in this series focus on the pivotal science and medical discoveries that changed the course of human history. Including both primary and secondary sources, each anthology traces the progression of scientific thought that made the discovery possible, chronicles the challenges faced by those now working in the field, and includes predictions about future developments and applications.
Includes bibliographical references and index.
Keywords: Cloning